EFFE-Escreves como falas - falas como escreves? - Lourenço-Gomes, Maria do Carmo (2016)
This paper introduces the project EFFE that applies and develops a methodology for data collection primarily intended for the study of the correlation between oral and written production in European Portuguese, and that also aims to serve a broad range of studies in different areas. It comprehends (i) a brief review of two scientific contexts occupied with learning to read and write, which are at the basis of the methodological planning of future corpora; (ii) the methodology adopted for the collection of speech and writing material of 48 children of a private school in Lisbon, and a summary of the quantitative data already observed; (iii) some considerations on unconventional forms (UF) observed in written production that reflect the speech of those children.